PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN SUB SEKTOR HOTEL, RESTORAN, DAN PARIWISATA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2017 - Tyara Dwi Putri (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2019)
The purpose of this study is to examine the influence of managerial ownership, institutional ownership and debt policy on the company in Sub Sector Hotel, Restaurant, and Pariwisata listed on the Indonesian Stock Exchange Period 2014-2017. The hypothesis testing was conducted using Multiple Linear Regressian. The study found that there is negative and significant relationship between managerial ownership, institutional ownership and debt policy.